Latvian registry of familial hypercholesterolemia: The first report of three-year results. (October 2018) - Latkovskis, Gustavs; Saripo, Vita; Gilis, Dainus; Nesterovics, Georgijs; Upena-Roze, Arta; Erglis, Andrejs
Abstract: Background and aims: Familial hypercholesterolemia (FH) was rarely diagnosed in Latvia before 2015, when the Latvian Registry of FH (LRFH) was established. Here, we report the first experience of the LRFH over three years (2015–2017). Methods: The LRFH is an ongoing nationwide, dynamic, long-term prospective cohort. The diagnosis of FH was assessed using the Dutch Lipid Clinic Network ( DLCN) criteria. Cascade screening of first-degree relatives using age- and sex-specific percentiles of low-density lipoprotein cholesterol (LDL-C) was performed in relatives of patients with definite and probable FH. Results: Among the 416 individuals included in the LRFH, 181 patients were diagnosed with FH (140 index cases and 41 relatives) and 151 with possible FH (not analysed in this report). The mean age was 51.3 ± 14.1 years, 38.1% (n = 69) were men and 35.4% (n = 64) had a history of premature coronary heart disease. Only 54.1% (n = 98) of patients were on any lipid-lowering therapy before inclusion in the LRFH. The maximal statin dose was used by 23.2% (n = 42), and only 4.4% (n = 8) had their LDL-C levels below the goal. The initial mean total and LDL-C levels were 7.7 ± 2.2 and 5.5 ± 2.1 mmol/L, respectively. In a subgroup of patients (n = 49) with follow-up, LDL-C levels were reduced from 6.1 ± 2.1 to 3.6 ± 1.7 mmol/L ( p < 0.001). Conclusions: An estimated 2.3% of FH patients in Latvia were diagnosed within three years. The vast majority of FH patients were under-recognized and poorly treated before their inclusion in the LRFH. Specialized care of FH patients within the frames of the registry substantially improved the management of this high-risk group. Highlights: The Latvian Registry identified 2.3% of FH patients within three years. Patients were poorly managed before inclusion in the Registry. Only 4.4% of patients had their LDL-C levels at goal before inclusion. Specialized care provided by the Registry substantially improved patient management.